MANAJEMEN PENDIDIKAN DAN PELATIHAN GURU DALAM MENINGKATKAN KOMPETENSI PROFESIONAL GURU - Sofia, Syahwa; Susanti, Try; Maryani, Ingka; Aprilla, Zulma; Pohan, Sulistyawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The quality of education heavily relies on teacher professional competence as a determinant factor. To elevate this capability, structured initiatives such as well-planned, systematic, and continuous training and education management are essential. This research intends to examine the management of teacher education and training aimed at fostering professional competence at MTs Nurul Iman Kenali Asam Atas, Jambi City. The investigation covers planning, execution, monitoring and evaluation, encountered challenges, and its subsequent influence on teacher professionalism. Utilizing a qualitative-descriptive design, data gathered from interviews, field observations, and documentation were scrutinized using the interactive analysis model of Miles, Huberman, and Saldaña (data condensation, data display, and verification). To guarantee data trustworthiness, both source and technique triangulations were deployed. The results show that the management of teacher training and education at MTs Nurul Iman has been implemented through the stages of planning, implementation, as well as evaluation and monitoring. Planning is conducted by identifying teacher competency needs, while implementation is realized through teacher participation in Subject Teacher Forums (MGMP), Teacher Professional Education (PPG), seminars, and online-based training. Evaluation and monitoring are carried out through academic supervision, classroom observation, discussions, and reviews of lesson plans as a basis for program improvement. The implementation of the program still faces constraints such as a limited number of educators, operational budget, and infrastructure. Nonetheless, training and education provide a positive impact on enhancing teacher professional competence, particularly in developing lesson plans, implementing more varied learning methods, and utilizing instructional media. This study demonstrates that the comprehensive application of management functions contributes to the effectiveness of training and education in improving teacher professional competence.